Spectroelectrochemical Behavior of Cr, Fe, Co, and Ni in LiCl-KCl Molten Salt for Decontaminating Radioactive Metallic Wastes. Issue 1 (29th January 2021) - Yoon, Seokjoo; Choi, Sungyeol
Abstract : This study examines the thermodynamic, kinetic, and spectroscopic behaviors of Cr, Fe, Co, and Ni to lay the foundation to develop an electrochemical decontamination process for radioactive metallic wastes. Cyclic voltammetry combined with numerical fitting was used to obtain the formal potentials, standard rate constants, and diffusion coefficients of redox reactions, Cr(II)/Cr, Fe(II)/Fe(0), Co(II)/Co(0), and Ni(II)/Ni(0), in LiCl-KCl at 773 K. The order of the diffusion coefficients was 10 –5 cm 2 s −1, which agrees with the existing data and the standard rate constants showed similar values with the order of 10 –3 cm s −1 between experimental correlations and numerical fitting. UV–vis-NIR absorption spectroscopy of the metallic constituents was performed to derive molar absorption coefficients and molecular structures in molten salt media. In particular, the redox reaction of Cr(III)/Cr(II) was investigated by chronoabsorptometry to obtain its formal potential, the number of electrons, and the diffusion coefficient of Cr(II). The obtained reaction properties were used in the numerical modeling of the ECE reaction in a Ni and Co binary system to reproduce the experimental results of CV, revealing the presence of chemical reaction. The findings of this study will be directly used for designing a decontamination process to produce acceptable waste forms and reduce waste volume.